Clinical leadership development in postgraduate medical education and training: policy, strategy, and delivery in the UK National Health Service - Aggarwal R; Swanwick T (Dove Medical Press, 2015)
Reena Aggarwal,1,2 Tim Swanwick2 1Women's Health, Whittington Health, London, UK; 2Health Education England, North Central and East London, London, UK Abstract: Achieving high quality health care against a background of continual change, increasing demand, and shrinking financial resource is a major challenge. However, there is significant international evidence that when clinicians use their voices and values to engage with system delivery, operational efficiency and care outcomes are improved. In the UK National Health Service, the traditional divide between doctors and managers is being bridged, as clinical leadership is now foregrounded as an important organizational priority. There are 60,000 doctors in postgraduate training (junior doctors) in the UK who provide the majority of front-line patient care and form an "operating core" of most health care organizations. This group of doctors is therefore seen as an important resource in initiating, championing, and delivering improvement in the quality of patient care. This paper provides a brief overview of leadership theories and constructs that have been used to develop a raft of interventions to develop leadership capability among junior doctors. We explore some of the approaches used, including competency frameworks, talent management, shared learning, clinical fellowships, and quality improvement. A new paradigm is identified as necessary to make a difference at a local level, which moves learning and leadership away from developing "leaders", to a more inclusive model of developing relationships between individuals within organizations. This shifts the emphasis from the development of a "heroic" individual leader to a more distributed model, where organizations are "leader-ful" and not just "well led" and leadership is centered on a shared vision owned by whole teams working on the frontline. Keywords: National Health Service, junior doctors, quality improvement, management, health care, leadership, fellowships, mentoring